Catalytic Depolymerization of Polyolefinic Plastic Waste. Issue 5 (8th March 2022) - Seitz, Mathias; Schröter, Stephan
Abstract: In a circular economy, processes such as the pyrolysis of polyolefin plastic waste must be established for naphtha cracker feedstock production. However, the composition of the plastic waste used has a strong influence on the conversion process and the heteroatom content, and thus on the quality of the pyrolysis oils. In this work, the influence of critical plastic components (e.g., polyamide 6) on the catalytic cracking of polyethylene (PE‐HD) in a batch rotary kiln reactor was investigated and a cost‐effective concept for integrating chemical recycling into a steam cracking plant was proposed. Abstract : Chemical recycling of plastic is proposed to close the carbon cycle. Catalysts, which have to be regenerated, can help to enhance the yield of desired products and to reduce energy consumption. The present studies reveal dependencies between catalyst design, poisons and reaction conditions in cracking of polyolefinic waste.